Localization to Bidirectional Languages for a Visual Programming Environment on Smartphones - Awwad, Aiman M Ayyal (International journal of computer science issues, 2017)
Catrobat is a free and open source visual programming environment for smartphones. It has been developed for educational purposes to help students visualize and understand learning material. It allows students to build their own animations and games for their classes in academic subjects and wirelessly control external hardware. Catrobat needs to talk to the young children in schools in their native language and enable them to get the best experience in the language of their choice. In this paper, we localize Catrobat into bidirectional languages such as Arabic, Persian, Urdu, and Hebrew, and introduce the challenging aspects of localization to such languages. The localization testing results show that the product is cosmetically correct, linguistically accurate, and culturally appropriate. Therefore, it meets bidirectional requirements, complies with bidirectionality design guidelines, and can be employed in programming education for young schoolchildren.